(untitled) (PerCursos, 2022)
In this article, we propose to enunciate approximations between the practices present in free fairs with central elements of the Amerindian philosophy of Good Living. Despite the strength of the retail market in the sale of food products, the free fair resists with its peculiar form and content, being an important space for commercialization of family and traditional farming productions and access to healthy foods. The relationships and sociability that take place in this space make the fair more than just a market, being a place of rhythm, meetings, walks, where people go to shop, to see friends, family, life stories. Therefore, our objective in this theoretical essay is to discuss the free fair as a space of resistance and an experience of good living, much more complex than the economistic logic is capable of understanding. Conviviality, collectivity, personality, informality, trust, territorial bond, secular knowledge, cultural appreciation, other modes of production and consumption are some of the many material and symbolic elements that represent the free fair as a plural space that is expressed in an ethics and values not exclusively market values. The fair is an experience of resistance that materializes itself in the daily life of the working class, whether they are producers, traders or consumers. Defending it, highlighting its social expression, which carries symbols contrary to Western modernity, is to promote the construction of ways to “postpone the end of the world” (KRENAK, 2019).